"Hero the other". Interknowledge networks and socio-educational trajectories in prisons in the south of the province of Santa Fe (Argentina) (Praxis Educativa, 2024)
Based on the elaboration of biographical accounts, we reconstructed the socio-educational trajectories of two adults deprived of their liberty in penitentiary institutions in the province of Santa Fe. The notion of socio-educational trajectories, articulated to a relational anthropological approach, alludes to the construction of paths that, at the level of the lived experience, include both structural aspects and the meaning they assume for the subjects. Likewise, we recover Michel De Certeau's category of trajectories, to account for the intersection of mobilities and modalities of action (tactics and strategies) included in these itineraries. The emerging analytical dimensions refer to the connections between the material, normative, organizational and relational conditions of the institutional locations in which the subjects' experiences are configured, and the knowledge and practices put into play in the course of their socio-educational trajectories, especially those anchored in the generation of interpersonal ties.
Keywords: detention itineraries; socio-educational trajectories; penitentiary circuit of central-southern Santa Fe; tactics and strategies